Pemurnian Biogas Dari Gas Pengotor Hidrogen Sulfida (H2S) Dengan Memanfaatkan Limbah Geram Besi Proses Pembubutan - Trisna Negara, Komang Metty; Tirta Nindhia, Tjokorda Gde; Sucipta, I Made; Atmika, I Ketut Adi; Putra Negara, Dewa Ngakan Ketut; Surata, I Wayan; Komaladewi, A.A.I.A. Sri (Jurnal Energi Dan Manufaktur; Vol 5 No 1 (2012): Oktober 2012)
This research is intended to utilize waste steel chips from the process of turning (process in which lathe machine is used) for purification of biogas from the gas of hydrogen sulfide (H2S) contaminant to support the promotion of zero waste industrial and manufacturing process in the world. The waste of Iron chips is collected and selected. Only long and spiral like of iron chips that are useful for this purpose. Since the chips having residual stress due to strain hardening during turning process, then the annealing process should be done before compacting to form a billet.The thickness of the billet was 1 cm and 6 cm in diameter with weight 500 gram. The annealing proces was carried out by burning the iron chip until reach the red color of fire. During the annealing process the iron inside the steel will react with oxygen to form iron oxide (Fe2O3) and if during oxidation there is a water vapor in the air then the iron bog ore Fe(OH)3 will be formed. Both of Fe2O3 and Fe(OH)3 are very reactive to H2S and therefore able to eliminate the H2S contaminant inside the Biogas. The billet is used as a filter and to be installed in the line of biogas distribution. The result indicate that the the iron chips is potential to be utilized to reduce the H2S contaminant in the biogas
Keywords: hydrogen sulfide, steel, chips, turning process, biogas